Multiannual financial perspective as a tool of local government unit development - Tomasz Wołowiec (e-Finanse: Financial Internet Quarterly, 2013)
The implementation of primary functions of local development management, especially its planning, organizing and controlling, cannot leave aside the financial aspects of these processes1. This can be attributed to the fact that every decision taken in the commune concerning strategic or operational management is related to the necessity of making specific financial contributions or to the conscious resignation from an opportunity to obtain income (via tax reliefs or exemptions). Moreover, the model of financial management adopted in a particular commune determines whether its financial methods and instruments perform development or stagnation functions. The implementation of primary functions of local development management, its planning, organizing and controlling in particular, cannot disregard the financial aspects of these processes.
Keywords: H6; H7; 330; multiannual; financial perspective; Local Government Units; finance management; Act Of Public Finance (PL)